Growing up with dyslexia: Child and parent perspectives on school struggles, self-esteem, and mental health - Wilmot, Adrienne; Pizzey, Hannah; Leitão, Suze; Hasking, Penelope; Boyes, Mark (WILEY, 2023)
Children with dyslexia, compared with typically reading peers, are at increased risk of internalising (e.g., anxiety) and externalising (e.g., aggression) mental health concerns; why this is the case is largely unknown. Our aim was to explore the socio-emotional experience of growing up with dyslexia from both child and parent perspectives. In so doing, we aimed to gain a better understanding of self-esteem and mental health in the context of dyslexia. One-to-one semi-structured interviews with 17 children with reading difficulties (aged 9–14 years; 16 with a diagnosis of dyslexia) and their mothers (interviewed separately) were analysed using Braun and Clarke's reflexive thematic analysis approach with a neurodiversity lens. We developed three themes to address the research aim: (1) Different in a good/bad way; (2) Exhausted and overwhelmed; and (3) It takes a community: Family school connections. Children discussed having “worries” and experiencing school-related stress and embarrassment. Mothers perceived children's internalising and externalising behaviour (meltdowns), school refusal, and homework resistance as emotional responses to children's school struggles due to poor “person-environment fit.” Our analysis highlights the particular importance of parent support, friendship, and school-connectedness for the wellbeing of children with dyslexia.